Good Faculty Governance and Control System to Create Academic Performance in University - Lely Kumalawati; Ulfa Rahmawati (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
Introduction/ Main Objectives: The aim of this study is to determine the influence of good faculty governance and control system to create good academic performance at the Faculty of Economics and Business in East Java. Over the last few decades, university performance has become a topic of interest, measured from different perspectives into multiple dimensions. with standard performance through accreditation, assessment, audit, and branding. Method: This study uses primary data collected using a questionnaire and distributed to lecturers at the Faculty of Economics and Business in East Java. Then, the results of the questionnaire were processed using linear regression analysis through the SPSS version 22.0 application. Result / Findings: The results of the study show that good faculty governance and control systems affect faculty performance based on Key Performance Indicators created by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia. Conclusion: The implication of this research is that ultimately the management at the faculty level must always continuously implement good governance. faculty governance and control systems to the maximum so that all the main performance indicators that have been set can be achieved optimally.